Efektivitas Penerapan Sistem Informasi Keuangan Desa Berdasarkan Peraturan Bupati Sidoarjo Nomor 7 Tahun 2020: Studi di Desa Pulungan - Kristiana Greta Calosa; Maulidah Narastri (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the effectiveness of implementing the Village Financial Information System (SISKEUDES) based on Sidoarjo Regent Regulation Number 7 of 2020, with a case study in Pulungan Village, Sedati District, Sidoarjo Regency. A descriptive qualitative approach was employed to obtain an in-depth understanding of how SISKEUDES supports village financial governance. Primary data were collected through semi-structured interviews with village officials directly involved in financial management, while secondary data were obtained from official documents and relevant regulations. The findings indicate that the implementation of SISKEUDES has significantly contributed to improving transparency, accountability, and efficiency in village financial management. The system facilitates orderly administration, accurate financial reporting, and easier supervision and auditing processes. However, several challenges remain, particularly related to the technical capacity of village officials, system stability, and the need for continuous training. SISKEUDES has proven to be an effective instrument for strengthening village financial governance, provided that it is supported by competent human resources and consistent institutional assistance from local governments.